Status of Stylosanthes development in other countries. I. Stylosanthes development and utilisation in South America - Miles, John W.; Lascano Aguilar, Carlos Eduardo (1997)
Research aimed at developing various Stylosanthes species as forage crops in South America began with the collection of Brazilian germplasm in the 1960s. These efforts have intensified greatly in the past 25 years with the participation of a number of local, national and international institutions. Eight cultivars have been released through the evaluation and selection of the resulting collections. However, the commercial success of these cultivars has ranged from limited to non-existent. Absence of commercial adoption is attributed to lack of interest in forage legume technology and to deficiencies in released cultivars. Poor persistence, commonly attributed to susceptibility to anthracnose, and problems with commercial seed production are perceived as major limitations of existing cultivars. Recent cultivar development projects in Brazil are based upon lessons learned from previous experience and may lead to expanded use of this valuable tropical legume genus.